Blended Learning at the Boundary: Designing a New Internship - Robert Heckman; Carsten S. Ã˜sterlund; Jeffrey Saltz (Online Learning, 2015)
This paper explores how blended learning can enhance learning at the boundary between academia and industry, and make possible the design of a new kind of internship. Boundary theory proposes that socio-cultural discontinuities between different environments create opportunities for learning. Blended learning pedagogy makes it possible to make the boundary between the classroom and the work place more salient and continuous. We present principles for designing internships that leverage blended learning to exploit boundaries, and describe an internship program based on these principles. Finally, we reflect on what we have learned through two years experience offering the program to students and employers.